Trends of transfusion transmittable infections among voluntary blood donors in a cardiac care hospital, Bengaluru, India - Sathyavathi Shivalingegowda; Krishnamurthy Banandur Nanjundappa; Umadevi Kannan; Manjunath Cholenahalli Nanjappa (International Journal of Medical Research and Review, 2019)
Introduction: Transmission of infectious diseases through donated blood is of concern to blood safety as transfusion forms an integral part of medical and surgical therapy. Blood transfusion carries the risk of transfusion-transmittable infections including HIV, hepatitis–B etc. Screening of voluntary donors who represent healthy population serves as a predictor for these dreadful diseases in healthy population.Materials and Methods: This retrospective study was conducted at the blood bank of Sri Jayadeva Institute of Cardiovascular Sciences and Research, Bengaluru. Data were analyzed for a period of 7 years from January 2011 to December 2017. All voluntary donors including replacement donors of our blood bank were screened for Hepatitis B Virus (HBV), Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV) and Syphilis infection by using ELISA.Results: The most common infection was Hepatitis B (0.69%) followed by Syphilis (0.34%) and HIV (0.0736%) and least with HCV (0.04%) in our study.Conclusion: This study has shown a decrease in seroprevalence for HIV and increase in seroprevalence for HCV over 7 years study period.